Análise redimensionada da tutela coletiva material e processual do direito fundamental à igualdade racial - Állan Felipe Brito Santiago (2020)
The objective of this study is to analyze the resizing of the material and procedural collective protection of the fundamental right to racial equality within a discourse that, established on the basis of a libertarian and transformative practice, aims to combat the use of law as a technique and instrument for perpetuating indignity ethnic-racial. Considering that the profound inequalities present in capitalist societies make social justice a matter of singular importance, seek to understand the material collective protection of the right to racial equality from the historical and sociocultural dimensions of economic and geographical redistribution, the recognition of the ethnic-affected by racism, prejudice and discrimination, and the resumption of the once lost humanity and dignity of blacks in Brazil. Although there are commonalities among the various countries that have adopted the socio-ideological regime of black slavery work, it is verified that the reality of each one presents specific challenges to be faced and the solutions must be thought out taking into consideration historical trajectory of each country. In this way each state creates and can extend its own list of social rights. Moreover, seek to prove that citizenship is the concrete means for each nation-state, whether through internal decisions and/or pressures from the international community, to achieve the goals of social justice. The extent of this justice in Brazil is measured by the effectiveness of state actions to enforce fundamental rights and the ability of citizens to pressure state agencies to meet their different demands in an equitable and symmetrical manner at all levels of society. In this context, it is understood that collective material law and collective procedural law can contribute to boost the review of public policies, ensure the protection of the right to racial equality and achieve the effectiveness of the fundamental objectives of building a free, just and fair society. solidarity, eradicating marginalization, reducing social inequalities and promoting the good of all, without prejudice of race, in accordance with the Constitution of the Republic of 1988, which advocates for the so-called Democratic State and Equal Law.